2019
DOI: 10.1111/avsc.12428
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation changes over the past two decades in a West African savanna ecosystem

Abstract: Questions: West African savanna ecosystems are affected by increasing land use intensity (e.g., agriculture and livestock herds) due to a growing human population. To understand the impact of land use intensification on savanna vegetation, we aim to answer the following questions: How do savanna species composition, diversity and structure change with increasing land use pressure? Are the impacts of land use change different in the woody and the herbaceous layers? Do the effects of land use change differ betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 46 publications
2
10
0
Order By: Relevance
“…Therefore, the gradient of area dedicated to agricultural activies not only results in changes in plant richness but also in changes in species composition by affecting the proportion of ruderal species. These results agree with those of Leßmeister et al [ 78 ], who reported a change in species composition and an overall increase in species richness derived from an increase in the proportion of ruderal and segetal species in modified landscapes of West African savanna. Despite the effect of percentage of crops in the landscape on plant richness, we did not find any effect of this variable on the Shannon’s diversity of plant species.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, the gradient of area dedicated to agricultural activies not only results in changes in plant richness but also in changes in species composition by affecting the proportion of ruderal species. These results agree with those of Leßmeister et al [ 78 ], who reported a change in species composition and an overall increase in species richness derived from an increase in the proportion of ruderal and segetal species in modified landscapes of West African savanna. Despite the effect of percentage of crops in the landscape on plant richness, we did not find any effect of this variable on the Shannon’s diversity of plant species.…”
Section: Discussionsupporting
confidence: 93%
“…The findings therefore show that abandonment of crop field as fallow can result into establishment of early successional species (pioneer) especially Annona senegalensis and Piliostigma thonningi (Ahmed, 1983; Donfack et al, 1995; Leßmeister et al, 2019; Oke & Jamala, 2013) in the first six years and if the fallow length is extended, late successional species such as Combretum collinum can be established without displacing the early successional species. This is reflected by occurrence of early successional species in old fallow albeit at relatively lower density.…”
Section: Discussionmentioning
confidence: 89%
“…insect attacks and wildfire), herbivory and land use (e.g. grazing and agriculture) (Belsky 1992;Leßmeister et al 2019). The current study, therefore, investigated the presence of abrupt changes in the NDVI time series and further assessed how PFTs are affected in terms of positive or negative magnitude changes (Figures 8(a, e), 10(a, b), Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…They are also more resistant to fire and can recover more easily after a fire once they have grown to a certain height and escaped the 'fire trap' de Bie et al 1998). A recent study by Leßmeister et al (2019) who studied vegetation changes over the past two decades in a West African savannah ecosystem found no change in woody species composition and richness over the past two decade studies while grass species have changed and species richness has increased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation